2020
DOI: 10.1111/1754-9485.13035
|View full text |Cite
|
Sign up to set email alerts
|

How accurately can multiparametric magnetic resonance imaging measure the tumour volume of a prostate cancer? Results of a systematic review

Abstract: Summary The tumour volume of a cancer within the prostate gland is commonly measured with multiparametric MRI. The measurement has a role in many clinical scenarios including focal therapy, but the accuracy of it has never been systematically reviewed. We included articles if they compared tumour volume measurements obtained by mpMRI with a reference volume measurement obtained after radical prostatectomy. Correlation and concordance statistics were summarised. A simple accuracy score was derived by dividing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Precision management of PCa has the potential to optimize therapy while preserving quality of life, but targeted treatment first requires accurate tumor localization. PI-RADS ROIs are known to underestimate tumor extent [8] , [9] , [10] , and in our study, treatment of the original ROI would have resulted in positive margins for every patient. It is clear that current multiparametric MRI contouring protocols, which were developed for diagnosis, are not suitable for targeted treatment.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Precision management of PCa has the potential to optimize therapy while preserving quality of life, but targeted treatment first requires accurate tumor localization. PI-RADS ROIs are known to underestimate tumor extent [8] , [9] , [10] , and in our study, treatment of the original ROI would have resulted in positive margins for every patient. It is clear that current multiparametric MRI contouring protocols, which were developed for diagnosis, are not suitable for targeted treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Leveraging a variety of ablative technologies [2] , [3] , [4] , [5] , [6] , FT has the potential to preserve quality of life while conferring metastasis-free and overall survival rates comparable with radical prostatectomy [7] . Most FT studies rely upon magnetic resonance imaging (MRI) to identify and delineate PCa foci, but MRI-visible regions of interest (ROIs) consistently underestimate the true size and extent of PCa [8] , [9] , [10] . Thus, treatment margins beyond MRI-visible tumor boundaries are critical to the success of FT.…”
Section: Introductionmentioning
confidence: 99%
“…Bezinque et al reported an excellent correlation between the PV calculated by the ellipsoid formula and MRI-R3D (manual segmentation by a radiologist) (ICC = 0.90), indicating that MRI using the ellipsoid formula provided an accurate measurement of PV [ 19 ]. In conclusion, PV estimation on MRI using the ellipsoid formula was a rapid technique with reasonable accuracy and reproducibility, and its general availability made it feasible for routine clinical use [ 23 ]. As in previous studies, our results demonstrated that the specimen volume for the entire cohort was highly associated with and underestimated by the volume measured by MRI [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data reflect the current situation whereby magnetic resonance imaging is not yet a diagnostic standard in prostate cancer care. Furthermore, there is accumulating evidence for the underestimation of prostate cancer expansion by multiparametric magnetic resonance imaging [ 27 ].…”
Section: Discussionmentioning
confidence: 99%